(3GdOQQ GdcHjQ aj efGbHs - (3jhSa Hf MSf Hf CMeO Hf MSf Hf YHO GdgGOj GdUGdMj, LeGd GdOjf, GHf GdeHQO,J (B909 (3g` s
(3ChdgG (B:s
(3jHJOF HJQLeI CMeO Hf CMeO Hf CMeO Hf eMeO GdbUQi s
(3BNQgG (B:s
(3jfJgi eG ajg Edi BNQ JQLeI Ydi HfCMeO , ef MQa GdYjf s
(3VGY ef GdCUd ebOGQ cdeIs
(3eQJH Ydi eMQha GdgLGAs
(3YdjgG ELGRI GdChdGOg HLhGQ QhGjJge ddcJGHs
(3gPG GdLRA ai efGbH GdTGaYjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B225 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B289s
Keywords: (3GdJGQjNs